Teacher Performance Management in Improving Learning Achievement of Elementary School Students - Ina Yuningsih; Ida Tejawiani (Journal of Innovation and Research in Primary Education, 2026)
Suboptimal teacher performance management implementation contributes to persistent low student achievement in Indonesian elementary education, yet limited research examines how contextual variations shape management effectiveness in resource-constrained rural settings. This qualitative comparative case study investigated teacher performance management across Armstrong's five-stage framework (planning, implementation, monitoring, assessment, follow-up) at two elementary schools in Naringgul District, Cianjur Regency. Data were collected through in-depth interviews with principals, teachers, and students; participatory classroom observations; and document analysis, then analyzed using Miles, Huberman, and Saldaña's interactive model. Both schools implemented all performance management stages systematically, though with distinct approaches: SDN Mulyasari employed backward design planning and spontaneous differentiated instruction despite infrastructure limitations, achieving 65% student competency attainment, while SDN Tegallame utilized behavioral objectives planning and programmatic differentiation with superior technology integration, achieving 75% attainment. The study revealed effective monitoring requires "nested feedback loops" combining classroom-level formative assessment with school-level clinical supervision. However, a critical implementation gap emerged: weak linkage between performance evaluation outcomes and targeted professional development interventions in both schools. Findings demonstrate that effective performance management permits multiple valid instantiations shaped by context, with pedagogical adaptability partially compensating for resource constraints. The research advances theoretical understanding by conceptualizing monitoring as synergistic multilevel systems while identifying the evaluation-to-development gap as a key barrier to transformative impact, suggesting educational leaders must prioritize systemic integration and establish explicit pathways connecting assessment to focused professional learning.